RNA polymerase pausing during initial transcription - Duchi, D; Bauer, D; Fernandez, L; Evans, G; Robb, N; Hwang, L; Gryte, K; Tomescu, A; Zawadzki, P; Morichaud, Z; Brodolin, K; Kapanidis, A (Cell Press, 2016)
In bacteria, RNA polymerase (RNAP) initiates transcription by synthesizing short transcripts that are either released or extended to allow RNAP to escape from the promoter. The mechanism of initial transcription is unclear due to the presence of transient intermediates and molecular heterogeneity. Here, we studied initial transcription on a lac promoter using single-molecule fluorescence observations of DNA scrunching on immobilized transcription complexes. Our work revealed a long pause ("initiation pause," ∼20 s) after synthesis of a 6-mer RNA; such pauses can serve as regulatory checkpoints. Region sigma 3.2, which contains a loop blocking the RNA exit channel, was a major pausing determinant. We also obtained evidence for RNA backtracking during abortive initial transcription and for additional pausing prior to escape. We summarized our work in a model for initial transcription, in which pausing is controlled by a complex set of determinants that modulate the transition from a 6- to a 7-nt RNA.